3D-MRI analysis of cartilage thickness changes after PRP injection in medial knee osteoarthritis: A preliminary report - Ichiro Sekiya; Hisako Katano; Mitsuru Mizuno; Kentaro Endo; Asuka Asami; Michiko Kajiwara; Naoki Otomo; Hideyuki Koga; Jun Masumoto; Nobutake Ozeki (PLoS ONE, 2025)
The regenerative effect of platelet-rich plasma injection on cartilage in knee osteoarthritis remains controversial. The purpose of this study was to use our recently developed 3D-MRI evaluation system to examine in detail the changes in cartilage thickness occurring six months after platelet-rich plasma injection. This study included 21 knees from 16 patients with medial knee osteoarthritis. An autologous protein solution (APS) was injected as platelet-rich plasma, and magnetic resonance imaging scans were taken before and six months after the injection. Cartilage thickness was quantified in seven regions using SYNAPSE 3D. Based on previous studies, the measurement error was set at 0.1 mm. The proportion of knees in which cartilage thickness increased (>0.1 mm) was highest in the anteromedial femoral region (43%); followed by the anterolateral femoral and lateral tibial regions (24%); the posterolateral femoral, patellar, and medial tibial regions (19%); and lowest in the posteromedial femoral region (14%). Notably, in the posteromedial femoral and medial tibial regions, which are primarily affected by medial osteoarthritis, less than 20% of the knees showed increased cartilage thickness. Our findings suggest that while platelet-rich plasma injection may have a positive effect on cartilage thickness in certain regions of the knee, its impact on the regions most affected by medial osteoarthritis appears limited.